The international encyclopedia of revolution and protest : 1500 to the present - Ness, Immanuel (Wiley-Blackwell, 2009)
Covers the history of protest and revolution over the past 500 years - throughout the modern era of mass movements. This title provides scholars and teachers and students with the information they need to understand the role and significance and origin of protest and revolution from 1500 onwards.